2015
DOI: 10.1002/2015ja021269
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and dynamical perturbations in the winter polar mesosphere‐lower thermosphere region associated with sudden stratospheric warmings under conditions of low solar activity

Abstract: The upper mesospheric neutral winds and temperatures have been derived from continuous meteor radar (MR) measurements over Sodankyla, Finland, in 2008–2014. Under conditions of low solar activity pronounced sudden mesospheric coolings linked to the major stratospheric warming (SSW) in 2009 and a medium SSW in 2010 are observed while there is no observed thermal signature of the major SSW in 2013 occurred during the solar maximum. Mesosphere‐ionosphere anomalies observed simultaneously by the MR, the Aura satel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…This annual variation is indeed typical for high latitudes because of the global atmospheric circulation [e. g., Andrews et al ., ]. Also, noticeable are temperature drops by about 20 K in January 2009 and 2010, which were associated with sudden stratospheric warmings (SSWs) [ Lukianova et al ., ]. Thus, the SGO MR data demonstrate agreement with commonly accepted concepts of mesosphere physics.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…This annual variation is indeed typical for high latitudes because of the global atmospheric circulation [e. g., Andrews et al ., ]. Also, noticeable are temperature drops by about 20 K in January 2009 and 2010, which were associated with sudden stratospheric warmings (SSWs) [ Lukianova et al ., ]. Thus, the SGO MR data demonstrate agreement with commonly accepted concepts of mesosphere physics.…”
Section: Introductionsupporting
confidence: 79%
“…Recently, similar comparison between SGO MR and Aura MLS data was performed for the event of sudden stratospheric warming in January 2009, and reasonable agreement of the temperature variations in both instruments was shown [ Lukianova et al ., ]. As an additional check, we calculated daily averaged temperature from the MR data obtained only for the 02–04 and 12–14 local time intervals to match to the Aura measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Both instruments have been operating since December 2008. Recently, a technique has been suggested to reveal the statistical characteristics of TIDs from the ionosonde data [Kozlovsky et al, 2013] and the MR measurements has been analysed to infer the signatures associated with a SSW [Lukianova et al, 2015].…”
Section: Es4003mentioning
confidence: 99%
“…In the mesosphere, air cooling is observed over the warming area in the stratosphere (Labitzke, , ). When studying upper mesospheric neutral winds and temperature over Sodankyla, Lukianova et al () observed pronounced mesospheric cooling, accompanied by a strong mesospheric wind shear of ~70 m/s/km during the 2009 major stratospheric warming. The cooling occurred 1 day earlier than the stratosphere maximum and was just about the same magnitude as the stratospheric warming (~50 K).…”
Section: Introductionmentioning
confidence: 99%
“…Yiğit and Medvedev () noted a possible role of gravity waves in vertical coupling between the lower and the upper atmospheres during SSW events. However, Lukianova et al (), based on meteor radar measurements, recorded the decay of gravity waves with 10–60‐min periods in the ionosphere over Sodankyla during the 2009 SSW.…”
Section: Introductionmentioning
confidence: 99%